Arts and power: policies in and by the arts - Gaupp, Lisa; Barber-Kersovan, Alenka; Kirchberg, Volker (Kunst und Gesellschaft, 2022)
.Establishing and De-Establishing Power in the Arts -- The Arts and the Power of Social Structures -- The Arts and the Dominance of Politics and Economic Order.